The myth and fallacy of simple extrapolation in medicine. - Fuller, Jonathan (Synthese, 2021)
Simple extrapolation is the orthodox approach to extrapolating from clinical trials in evidence-based medicine: extrapolate the relative effect size (e.g. the relative risk) from the trial unless there is a compelling reason not to do so. I argue that this method relies on a myth and a fallacy. The myth of simple extrapolation is the idea that the relative risk is a 'golden ratio' that is usually transportable due to some special mathematical or theoretical property. The fallacy of simple extrapolation is an unjustified argument from ignorance: we conclude that the relative effect size is transportable in the absence of evidence to the contrary. In short, simple extrapolation is a deeply problematic solution to the problem of extrapolation.